الأموال المجنبة بالمؤسسات المالية الإسلامية: مفهومها، الأحكام الشرعية المتعلقة بتحصيلها وأحوال الاستفادة منها = Provisioned funds in Islamic financial institutions: their concept, Shariah rulings related to their collection, and conditions for benefiting from them - Zakariyah, Habeebullah; Bessais, Sofien; noor, Azman Mohd Noor (2024)
This study is an analytical examination from a Shariah perspective of provisioned funds in Islamic financial institutions (IFIs). The issue concerns the collection of these funds by IFIs, which should not be considered as part of their profits nor should they directly or indirectly benefit from them. The aim of this study is to explore the juristic opinions regarding the collection of these funds and the extent to which it is permissible to benefit from them based on their sources and circumstances. The research employed a qualitative approach, focusing primarily on information related to provisioned funds and the relevant Shariah rulings from previous studies. The study identified the primary sources of provisioned funds for IFIs, as well as the Shariah opinions pertaining to the collection of these funds and the circumstances under which these institutions can benefit from them. In conclusion, the study recommended that IFIs prioritize adherence to Shariah governance standards and regulations, whether internal to the institution or set forth by official regulatory bodies such as central Shariah supervisory bodies. Additionally, the study suggested compliance with standards issued by specialized and accredited bodies, such as AAOIFI standards, to minimize the reliance on provisioned funds as much as possible.